2019
DOI: 10.3390/ijerph16193522
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability and Influencing Factors of Aerosol Optical Depth over the Pan Yangtze River Delta during the 2014–2017 Period

Abstract: Large amounts of aerosol particles suspended in the atmosphere pose a serious challenge to the climate and human health. In this study, we produced a dataset through merging the Moderate Resolution Imaging Spectrometers (MODIS) Collection 6.1 3-km resolution Dark Target aerosol optical depth (DT AOD) with the 10-km resolution Deep Blue aerosol optical depth (DB AOD) data by linear regression and made use of it to unravel the spatiotemporal characteristics of aerosols over the Pan Yangtze River Delta (PYRD) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…As it is likely that collinearity exists in the predictive variables, the variance inflation factor (VIF) [57,61] is used to examine it in this study: Although 192 vegetation quadrats were initially selected, only 140 quadrats of them (shown in Figure 1) were visited and investigated in practice-because some of the pre-selected quadrats were not accessible for various reasons (e.g., physical barriers and refusal to access). Among the 140 quadrats were 35 dominated by coniferous forest, 73 by broadleaved forest, and 32 by low vegetation.…”
Section: Stepwise Regression Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is likely that collinearity exists in the predictive variables, the variance inflation factor (VIF) [57,61] is used to examine it in this study: Although 192 vegetation quadrats were initially selected, only 140 quadrats of them (shown in Figure 1) were visited and investigated in practice-because some of the pre-selected quadrats were not accessible for various reasons (e.g., physical barriers and refusal to access). Among the 140 quadrats were 35 dominated by coniferous forest, 73 by broadleaved forest, and 32 by low vegetation.…”
Section: Stepwise Regression Modelingmentioning
confidence: 99%
“…As it is likely that collinearity exists in the predictive variables, the variance inflation factor (VIF) [57,61] is used to examine it in this study:…”
Section: Stepwise Regression Modelingmentioning
confidence: 99%
“…Regarding PRE, daily PRE with cumulative values were also rescaled to monthly, seasonal, and annual temporal resolutions. After interpolation by inverse distance weighting, monthly, seasonal, and annual PRE maps were generated [18,109]. The maximum and minimum total annual PRE in 2017 was 1020.15 mm and 99.80 mm, respectively (Figure 2b).…”
Section: Topographic Datamentioning
confidence: 99%
“…where R i represents the correlation coefficient between the i th predictive variable and the remaining predictive variables. No multicollinearity exists if VIF is less than 3 [109,113].…”
Section: Stepwise Multilinear Regression Modelingmentioning
confidence: 99%
“…For example, the shortcomings of the DT algorithm and DB algorithm for AOD detection in bright areas, the errors of cloud detection in some heavily polluted areas and the degradation of other sensors directly affect the detection of dark pixels in low angle areas, which leads to the loss of AOD data in some areas [26,27]. A study of the Yangtze River Delta in China found that the missing rate of MOD AOD reached 89.6% between 2014 and 2017 [28]. Because the results of AOD are affected by meteorological conditions, human activities and vegetation coverage, it is difficult to ensure the accuracy of the AOD restoration [29].…”
Section: Introductionmentioning
confidence: 99%